A practical guide to Red Hat Linux : Fedora Core and Red Hat Enterprise Linux - Sobell, Mark G. (Prentice Hall, 2006)
"This book explains Linux clearly and effectively - with a focus on features you care about, from system security and Internet, server setup to Windows file/printer sharing. Best selling author Mark Sobell starts at the beginning and walks you through everything that matters, from installing Linux using the included DVD to working with CNOME, KDE, Samba, sendmail, Apache, DNS, NIS, and iptables." "This edition contains extensive coverage, including full chapters on using Linux from the command line and GUI: even more thorough system administration and security guidance; and up-to-the-minute, step-by-step instructions for setting up networks and every major type of Internet server. Along the way, you learn the "hows" and the "whys.""--Jacket.